Monocyte chemotactic protein 1 (MCP-1) modulates pro-survival signaling to promote progression of head and neck squamous cell carcinoma. - Wen-Tsai Ji; Hau-Ren Chen; Chun-Hsuan Lin; Jeng-Woei Lee; Ching-Chih Lee (PLoS ONE)
Background Monocyte chemotactic protein-1 (MCP-1) recruits monocytes and macrophages to inflammation sites, and inflammatory infiltration correlates with the progression of head and neck squamous cell carcinoma (HNSCC). This study aims to determine whether MCP-1 expression is related to HNSCC malignancy and patient survival. We also investigated the relationship between MCP-1 expression and the phosphorylation state of the pro-survival pathway factors Akt, ERK, and STAT3. Methods Expression of MCP-1 and related proteins in HNSCC cell lines was investigated using western blotting. HNSCC patients (34) without distant metastasis at diagnosis were recruited for tissue specimen evaluation of MCP-1 expression and clinical outcomes. The relationship between MCP-1 expression and survival was evaluated using the Cox proportional hazard model with stepwise selection. Results High-grade HNSCC cell lines were found to have higher levels of active Akt, ERK, and/or STAT3 than did lower grade cell lines under serum-free condition. OCSL, the most malignant cell line, had the highest level of endogenous MCP-1. Administration of exogenous recombinant MCP-1 increased phosphorylation of Akt, ERK, and STAT3 in a dose- and time-dependent manner and increased cellular resistance to serum starvation. Inhibition of Akt, ERK, or STAT3 reduced cell growth and caused cell death. Long-term survival of HNSCC patients was negatively associated with the histological intensity of MCP-1, implicating MCP-1 as a potential prognostic marker for HNSCC. Conclusions These results suggest that overexpressed MCP-1 in cancer cells may promote HNSCC progression through upregulating pro-survival signaling pathways. High cellular MCP-1 expression is related to poor overall survival rate in HNSCC patients.